Using unified modeling language for conceptual modelling of knowledge-based systems - Abdullah, Mohd Syazwan; Benest, Ian; Paige, Richard; Kimble, Chris (Springer Berlin Heidelberg, 2007)
This paper discusses extending the Unified Modelling Language by means of a profile for modelling knowledge-based system in the context of Model Driven Architecture (MDA) framework. The profile is implemented using the eXecutable Modelling Framework (XMF) Mosaic tool.A case study from the health care domain demonstrates the practical use of this profile; with the prototype implemented in Java Expert System Shell (Jess).The paper also discusses the possible mapping of the profile elements to the platform specific model (PSM) of Jess and provides some discussion on the Production Rule Representation (PRR) standardisation work.